Implementation of Islamic Microfinance through Marketing Strategy for Financing Rural Communities in Cirebon Region - Sukarnoto, Toto; Cahyono, Heru; Karjuni, Agus; Anwar, Mohamad; Kasheem, Majdy (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2025)
Microfinance provides access to financial services for low-income people, empowering and increasing business productivity in achieving prosperity. Rural communities are the group most interested in microfinance because it is often neglected by the formal financial system. This research focuses on the characteristics of rural communities in improving the implementation of microfinance through financing marketing strategies. A descriptive qualitative approach is used in this study. The data sources are based on observations, in-depth interviews, and contextual literacy of various documents. The research respondents were female entrepreneurs who received sharia-based microfinance facilities from BTPN Syariah and PT Permodalan Nasional Madani in the Cirebon area. The data analysis techniques were carried out through Data collection, Data reduction, Data presentation, Conclusion drawing/verification. The implementation of sharia microfinance through financial institutions and financing institutions in the Cirebon area has proven to have a positive effect. The marketing strategy of Islamic microfinance institutions in rural communities helps the growth of sustainable micro enterprises. This is evidenced by the ease of access to financing and more flexible terms in applying for financing, being able to increase sales results, and a community approach to financing through rural women entrepreneurs that helps reduce unemployment and poverty rates. The economic impact in the application of the concept of sharia economics encourages the principles of justice and social welfare, in addition to being able to provide access to capital. The implementation of sharia microfinance in rural communities in Cirebon has positive and transformative implications for the economy and social of the community by increasing access to financing, encouraging the growth of micro businesses, empowering women, reducing poverty and dependence on loan sharks, although it is still faced with the challenges of limited capital, low Islamic financial literacy, and the need for adequate regulatory support